DESIGN OF UNMANNED GRENADE TAMER PROTOTYPE WITH WIRELESS CONTROL - Aris Tri Ika Rahmadi; Ayip Rivai Prabowo; Ali Mashudi; Luqman Arif (JOURNAL ASRO, 2020)
Puslatdiksarmil is a military training and basic education center. To support the trainer in securing the grenadeduring the grenade throwing exercise, the author made "Design of Prototype Unmanned Grenade Tamer withWireless Control. This tool is used to assist the trainers in the implementation of handling unexploded grenades,by placing a detonator on the grenade then blasting. In the robot control application is very necessary ineveryday life and is very helpful in human activities that are dangerous and difficult to do by humans andtherefore we need an application that can control the robot remotely. In this Final Project, a robot has beendesigned that can be controlled remotely by air or wireless media as an application of a grenade tamer robot.Where the design of this robot will use an integrated robot with an actuator to drive the robot, a camera tomonitor the location of objects and its surroundings, and a wireless module that has been connected with the2.4 Ghz Tranciever so the robot can now be monitored remotely to perform operations.Keywords: Unmanned, Wireless, 2.4Ghz Frequency